Impact of low versus high fluidic settings on the efficacy and safety of phacoemulsification. (20th June 2013) - Schriefl, Sabine M.; Stifter, Eva; Menapace, Rupert
Abstract. Purpose: To compare intraoperative efficiency and postoperative outcomes of cataract surgery with low and high fluidic settings. Methods: In this prospective, randomized, single‐blinded study, 114 eyes of 57 patients were operated with low fluidic settings for one eye (group I) and high fluidic settings for the other eye (group II). Efficiency was judged as metred surgery time, effective phacoemulsification time (EPT) and the amount of balanced salt solution used. Visual outcome and endothelial cell count were determined 1 week and 18 months postoperatively. Results: The overall effective phacoemulsification energy was statistically significantly lower (p = 0.003) in group II than in group I. Conquest of the nuclei was achieved with about two‐thirds of the energy needed in group I, with 6.59 ± 4.79 effective ultrasound energy compared with 3.99 ± 3.18 (p = 0.001). Overall, about 12% more solution was used in group II than in group I. Median visual acuity was 1.0 for both groups 18 months after surgery. The mean endothelial cell loss was 5.0% in eyes in group I compared with 6.3% in eyes in group II (p > 0.5). Conclusion: Switching from low fluidic settings with a conventional coaxial 20G phacoemulsification tip to higher fluidic settings with a microcoaxial phaco tip statistically significantly decreases EPT. As only marginally more solution was used with the higher aspiration flow, occlusion must be accomplished more often with high than with low fluidics. Aspiration of the quadrants was therefore more efficient with high fluidic settings. The enhanced pump speed did not result in more tissue damage.